2018
DOI: 10.1007/s11901-018-0394-x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Elimination of Hepatitis C Virus Infection as a Public Health Threat in the United States

Abstract: Purpose of Review Direct-acting antiviral regimens for chronic hepatitis C virus (HCV) became available in 2014, and these highly curative therapies have the potential to reduce HCV-associated morbidity and mortality, decrease transmission, and eliminate HCV infection as a public health problem. This review summarizes the recommendations by the National Academies of Sciences, Engineering, and Medicine for a US strategy for HCV elimination. Recent Findings To achieve proposed targets of reducing HCV incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…(1,(6)(7)(8) When more effective, curative direct-acting antiviral medications for hepatitis C became available in 2014, hepatitis C elimination became an imaginable goal for the first time. (9,10) States and public health coalitions have begun launching hepatitis C elimination strategies to scale up primary prevention, testing, and treatment interventions. (11)(12)(13) However, hepatitis C surveillance data for monitoring progress of such initiatives are limited.…”
mentioning
confidence: 99%
“…(1,(6)(7)(8) When more effective, curative direct-acting antiviral medications for hepatitis C became available in 2014, hepatitis C elimination became an imaginable goal for the first time. (9,10) States and public health coalitions have begun launching hepatitis C elimination strategies to scale up primary prevention, testing, and treatment interventions. (11)(12)(13) However, hepatitis C surveillance data for monitoring progress of such initiatives are limited.…”
mentioning
confidence: 99%
“…In spite that many countries have published their strategies to achieve the WHO 2030 hepatitis C elimination objective, 13–22 up to our knowledge there is not so much published information about how hepatitis C treatment is starting to impact on hospitalization rates. Two studies were found developed in Canada 23 and Australia 24 that reported a similar experience to ours with a significant decline in the hospitalization rates after 2015, in the direct‐acting antivirals era.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Various interventions have been de-veloped to address the unmet needs of HCV care in rural populations, but the effect of these interventions remains unclear. [8][9][10][11][12] Developed in 2003, the Project Extension for Community Healthcare Outcomes aims to use telementoring, a guided practice model where primary care phycisians (PCPs) keep managing patients through tele-education with specialists at academic health centers, to help PCPs in rural areas of New Mexico manage HCV patients. [13][14][15] In our previous research, we found that a telementoring, task-shifting model helped reduce urban-rural disparities in HCV treatment possibly through educating rural primary care providers to accumulate knowledge and confidence in using highly effective and well-tolerated direct-acting antiviral agents (DAAs) to treat HCV patients.…”
Section: Introductionmentioning
confidence: 99%
“… 3–7 Various interventions have been developed to address the unmet needs of HCV care in rural populations, but the effect of these interventions remains unclear. 8–12 …”
Section: Introductionmentioning
confidence: 99%